2013
DOI: 10.21273/hortsci.48.10.1275
|View full text |Cite
|
Sign up to set email alerts
|

Ripening-dependent Changes in Phytonutrients and Antioxidant Activity of Red Pepper (Capsicum annuum L.) Fruits Cultivated under Open-field Conditions

Abstract: To understand ripening-dependent changes in phytonutrients, five commercial cultivars of red peppers (Capsicum annuum L.) grown in an open field in Taean, South Korea, were selected and their fruits were harvested at green mature (GM), intermediate breaker (BR), and red ripe (RR) stages and their phytonutrient contents and antioxidant activities were compared. Three major patterns in relation to ripening progress were observed. First, continuous increases were observed in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 53 publications
6
37
0
2
Order By: Relevance
“…To a lesser extent, the year effect also contributed significantly to the variation in total flavonoids and most individual flavonoids (except for myricetin), which confirms the importance of a multi‐year design to decrease the environmental effect related to agroclimatic conditions from year to year, especially in open fields . The ripening stage (R) also contributed significantly in all flavonoids, particularly in myricetin (Table ), indicating changes in the content of phenolics due to the ripening process . By contrast, the general effect of the growing system (E) was not significant, although significant G × E interaction was found for variation in total flavonoids ( P < 0.05) and luteolin ( P < 0.01), suggesting a different behavior of the accessions depending on the growing system.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…To a lesser extent, the year effect also contributed significantly to the variation in total flavonoids and most individual flavonoids (except for myricetin), which confirms the importance of a multi‐year design to decrease the environmental effect related to agroclimatic conditions from year to year, especially in open fields . The ripening stage (R) also contributed significantly in all flavonoids, particularly in myricetin (Table ), indicating changes in the content of phenolics due to the ripening process . By contrast, the general effect of the growing system (E) was not significant, although significant G × E interaction was found for variation in total flavonoids ( P < 0.05) and luteolin ( P < 0.01), suggesting a different behavior of the accessions depending on the growing system.…”
Section: Resultsmentioning
confidence: 78%
“…37 The ripening stage (R) also contributed significantly in all flavonoids, particularly in myricetin (Table 2), indicating changes in the content of phenolics due to the ripening process. 38 By contrast, the general effect of the growing system (E) was not significant, although significant G × E interaction was found for variation in total flavonoids (P < 0.05) and luteolin (P < 0.01), suggesting a different behavior of the accessions depending on the growing system. Also, G × R interaction was significant for total and individual flavonoids.…”
Section: Resultsmentioning
confidence: 80%
“…Similary X. caffra and S. cocculoides have higher amounts of phenolic contents compared to domesticated fruits that are commonly used by communities such as mango and banana (440.6 and 362.4 mg GAE/100 g respectively) as reported by Singh et al, (2016) and papaya (272.99 to 339.91 mg GAE/100g) reported by Maisarah et al (2013). Phenolics are important group of bioactive compounds in plant materials that have antioxidant properties for human health (Bhandari et al, 2013). The findings of this study indicate that indigenous fruits are superior in total phenolic contents compared to domesticated fruits and they should be regarded as an important source of natural antioxidant in the human diet.…”
Section: Phenolic Contentsmentioning
confidence: 81%
“…Jarret et al [5] showed the great diversity of free sugars within the C. chinense gene pool. Further, free sugar quantity was affected by pepper cultivars, fruit maturation, cultivation region, and year in Korea [10,16,38]. The contents of fructose and glucose across varieties were higher in peppers produced from IS than those of YY and both compounds significantly varied by year ( Table 5).…”
Section: Capsaicinoid and Free Sugar Compositionsmentioning
confidence: 99%
“…Even within the same variety, nutritional composition of peppers varies depending on developmental stages, growing regions, and agricultural practices [10][11][12][13][14]. Pérez-López et al [14] showed that levels of ascorbic acid, total carotenoid, phenolic, and mineral were affected by the fruit maturation and types of agricultural practice.…”
Section: Introductionmentioning
confidence: 99%